A importância do empreendedorismo na gestão pública: o caso da Feira do Jovem Empreendedor Joseense - Lima, Sheila Morais Faria (2012)
Entrepreneur is the person who develops their social proactively with leadership and commitment, achieving, in an innovative way to engage in these efforts play in achieving your goals. Entrepreneurs are noted for their great creativity, innovation, leadership, initiative, commitment, flexibility, boldness and confidence. This study is expected to show the importance of entrepreneurship for a quality public management, as well as the performance hall in the definition and implementation of public policy entrepreneur, managed and disseminated to servers via the Fair Young Entrepreneur Joseense. Through a staff of public managers entrepreneurs, public agencies be able to comply with the principle of the supremacy of the public interest, because the social demands will be better understood and met more quickly and effectively. The behavior of public managers should target the public interest, seeking to fulfill it with effectiveness and commitment to quality in public management is achieved. This study analyzes the entrepreneurial action of São José dos Campos, which develops actions / policies aimed at developing its servers entrepreneurship, seeking to improve the quality of public service delivery.